2022
DOI: 10.3389/fonc.2022.991451
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tRF-1:29-Pro-AGG-1-M6 and tRF-55:76-Tyr-GTA-1-M2 as novel diagnostic biomarkers for lung adenocarcinoma

Abstract: ObjectiveTRNA-derived fragments (tRFs) and tRNA-derived stress-induced RNAs (tiRNAs) are recognized as novel and potential types of non-coding RNAs (ncRNAs), and several tRF/tiRNA signatures are closely associated with tumor diagnosis. This study aimed to analyze the expression profiles of plasma tRFs/tiRNAs and to clarify their diagnostic value in lung adenocarcinoma (LUAD).MethodsThe differential expression profiles of plasma tRFs/tiRNAs in patients with four patients with early LUAD, four patients with adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Since lung adenocarcinoma is one of the most prevalent cancer types and one of the malignant tumors with the maximum mortality and morbidity, understanding the molecular mechanism of CD39 may assist in the discovery of clinically effective therapies or exploration of compelling predictive biomarkers ( 21 ). Many studies have shown that CD39 is crucial to the development and progression of many cancers and diseases ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since lung adenocarcinoma is one of the most prevalent cancer types and one of the malignant tumors with the maximum mortality and morbidity, understanding the molecular mechanism of CD39 may assist in the discovery of clinically effective therapies or exploration of compelling predictive biomarkers ( 21 ). Many studies have shown that CD39 is crucial to the development and progression of many cancers and diseases ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated promising levels of sensitivity and specificity of tsRNAs observed in tumor tissues and body fluids. The abnormal expression patterns of tsRNAs identified in patients with tumors highlight their potential to act as a new biomarker for tumor diagnosis [ 166 173 ] (table 3 ). In their study, you et al [ 166 ] identified a downregulation in tRF-1:29-Pro-AGG-1-M6 expression in the plasma of patients with LUAD via tRF/tiRNA sequencing.…”
Section: Clinical Application Value Of Tsrnas In Cancersmentioning
confidence: 99%
“…The abnormal expression patterns of tsRNAs identified in patients with tumors highlight their potential to act as a new biomarker for tumor diagnosis [ 166 173 ] (table 3 ). In their study, you et al [ 166 ] identified a downregulation in tRF-1:29-Pro-AGG-1-M6 expression in the plasma of patients with LUAD via tRF/tiRNA sequencing. In contrast, an upregulation in tRF-55:76-Tyr-GTA-1-M2 expression was also observed, which was consistent with qRT-PCR results.…”
Section: Clinical Application Value Of Tsrnas In Cancersmentioning
confidence: 99%